Characteristics of nurses-physicians communication for patient safety - Fuentes-Colmenero, Ana Luisa (Revista Española de Comunicación en Salud, 2019)
Communication enables the establishment of professional links, facilitating interdisciplinary collaboration, as well as the elaboration of joint plans. Interprofessional communication problems during usual care activity can be transformed into information errors that affect patient safety. Objective: To analyze the variables, themes and categories that characterize the communication between nursing and medical professionals for safe health care. Methodology: A systematic review of the primary studies published in electronic databases in English and Spanish on communication between nursing and medical professionals was carried out. Results: Seventeen studies met the criteria of the review. Both quantitative and qualitative studies showed that speaking clearly and precisely favored patient safety. On the contrary, the use of indirect language or its inhibition hindered effective interprofessional communication. In qualitative studies, nursing professionals recommended the maintenance of a respectful professional attitude, collaboration, professional recognition and greater listening. Conclusions: There is a general absence of cross-cultural adaptation and validation of questionnaires in quantitative studies. Most of the studies are limited to special services care settings. More studies in hospitalization are needed.